PEMANFAATAN TEKNOLOGI PLASMA UNTUK MENINGKATKAN KADAR NITROGEN DAN PROTEIN PELLET PAKAN SAPI DARI LIMBAH TANAMAN JAGUNG - M. Shobarudin; Muhammad Nur (Youngster Physics Journal, 2013)
Research has been done on the levels of plasma radiation influence elements of nitrogen and protein samples of cow feed pellets from waste corn plant. Plasma being used in this study are positive corona plasma, which are generated using high voltage direct current (DC) with multiple point to plane electrode configuration, where the distance between the electrodes of 2.5 cm.On the research of this variable are used i.e. with voltage variations of quantity (3-9.5) kV, where the samples without treatment used as controls. Plasma reactor used in the research of electrode of multi point to plane, in which the electrodes point is connected to the positive electrode. Distance between electrodes of 2.5 cm.High electrical field strength around the electrodes can ionize the gas molecules of nitrogen around the active electrode. Ions of nitrogen is depositioning to the sample, so would the levels of nitrogen. Voltage variations can affect the amount of ions formed thereby affecting the levels of nitrogen samples. From this research conclusion effective voltage plasma radiation occurs at voltage 4 kV with levels of nitrogen 1.169% or the equivalent of 7.30% protein. These results meet minimum standards of proteins, suggested by Parakkasi (1999) of 7%.Keywords: plasma, ion, pellets, nitrogen, protein.